ION-EXCHANGE RESINS AS INGREDIENTS DRUG FORMULATIONS - N. B. Demina; D. D. Vorobyeva (Разработка и регистрация лекарственных средств, 2019)
The article discusses the usage of ion-exchange resins (IOSs) as excipients and pharmaceutical substances. The main functions of IOSs as excipients are: taste masking, disintegration of tablets, stabilization of substances, modified release, etc. Were described the examples of IOSs usage in oral, ophthalmic, nasal, transdermal dosage forms. Good technological properties: solid, liquid, application.